An Empirical Evaluation of Egg Demand in the United States. (May 2021) - Bakhtavoryan, Rafael; Hovhannisyan, Vardges; Devadoss, Stephen; Lopez, Jose
Abstract: We adopt an EASI model to estimate demand for omega-3, organic, cage-free, and conventional eggs in the United States. Our empirical framework accounts for demand inter-dependencies among these egg types, while allowing for unrestricted Engel curves, unobserved consumer heterogeneity, and a broader product and geographic coverage. We further address endogeneity of prices and expenditures and left-censoring induced by disaggregate data. Our results indicate that the demand for organic and cage-free eggs is price-elastic, while the demand for omega-3 and conventional eggs is price-inelastic. Additionally, we establish strong substitutability relationships between the eggs. Finally, we measure consumer welfare consequences of rising domestic egg prices brought by Japan's egg import tariff reductions.